AK-1-FIT reconstructed temperature record - Paul S Wilcox (PANGAEA, 2023)
The dataset includes speleothem fluid inclusion hydrogen isotope data used to reconstruct temperature in southeastern Alaska during the Holocene. The AK-1-FIT record is a composite record and incorporates data from speleothem EC-17-7-A and WB-21-5-A. Speleothem EC-17-7-A was collected in July 2022 from El Capitan Cave (56.170 N, -133.320 E; 80 m.a.s.l) and speleothem WB-21-5-A was collected in May 2022 from Wishbone Cave (55.774 N, -133.191 E; 420 m.a.s.l.). The data collection was completed between 2022 and 2023. Fluid inclusion hydrogen isotope samples were measured on a ThermoFisher Delta V isotope ratio mass spectrometer.
In: Wilcox, PS (2023): AK-1-FIT fluid inclusion data [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.964355